2015
DOI: 10.1097/aln.0000000000000414
|View full text |Cite
|
Sign up to set email alerts
|

Pretransfusion Testing and Transfusion of Uncrossmatched Erythrocytes

Abstract: Pretransfusion testing is reviewed for the anesthesiologist, with an emphasis on the electronic crossmatch and transfusion of uncrossmatched erythrocytes when testing is incomplete.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 21 publications
0
23
0
5
Order By: Relevance
“…This process makes prompt transfusion in the early trauma stage very difficult. To solve this issue, some have suggested transfusing universal donor blood (O in ABO typing and Rh [-]) in early trauma, during the full screening for transfusion [ 22 ]. Many studies have shown that the mortality did not increase significantly using this approach [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This process makes prompt transfusion in the early trauma stage very difficult. To solve this issue, some have suggested transfusing universal donor blood (O in ABO typing and Rh [-]) in early trauma, during the full screening for transfusion [ 22 ]. Many studies have shown that the mortality did not increase significantly using this approach [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The emergency provision of uncross‐matched group O RBC units is a common practice at trauma centres as the perceived risk of a clinically significant adverse reaction is relatively low and outweighed by the potential benefits of immediate RBC transfusion to a patient at high risk of fatal haemorrhage (Murthi et al, ; Boisen et al, ). This is particularly the case given that young males are most often trauma victims (Norton & Kobusingye, ) and less likely than females to harbour RBC‐reactive alloantibodies (Barnes, ) that could be harmful when an incompatible RBC unit is given before completing serological testing.…”
mentioning
confidence: 99%
“…14 It involves proper requisition, compatibility testing and pre-release checks 15 that includes ABO typing, Rh typing, antibody screening, antibody identification and crossmatch. 16 Pre-transfusion testing and procurement of proper blood and/or its component can be hindered by an incomplete request form. 17 Request forms are very important to convey proper message from a physician to the blood bank, laboratory or radiological services.…”
Section: Discussionmentioning
confidence: 99%